The SCUBA-2 Cosmology Legacy Survey: the clustering of submillimetre galaxies in the UKIDSS UDS field - Wilkinson, Aaron; Almaini, Omar; Chen, Chian-Chou; Smail, Ian; Arumugam, Vinodiran; Blain, Andrew; Chapin, Edward L.; Chapman, Scott C.; Conselice, Christopher J.; Cowley, William I.; Dunlop, James S.; Farrah, Duncan; et al. (Oxford University Press, 2017)
Submillimetre galaxies (SMGs) are among the most luminous dusty galaxies in the Universe, but their true nature remains unclear; are SMGs the progenitors of the massive elliptical galaxies we see in the local Universe, or are they just a short-lived phase among more typical star-forming galaxies? To explore this problem further, we investigate the clustering of SMGs identified in the SCUBA-2 Cosmology Legacy Survey. We use a catalogue of submillimetre (850 μm) source identifications derived using a combination of radio counterparts and colour/infrared selection to analyse a sample of 610 SMG counterparts in the United Kingdom Infrared Telescope (UKIRT) Infrared Deep Survey (UKIDSS) Ultra Deep Survey (UDS), making this the largest high-redshift sample of these galaxies to date. Using angular cross-correlation techniques, we estimate the halo masses for this large sample of SMGs and compare them with passive and star-forming galaxies selected in the same field. We find that SMGs, on average, occupy high-mass dark matter haloes (Mhalo > 1013 M_) at redshifts z > 2.5, consistent with being the progenitors of massive quiescent galaxies in present-day galaxy clusters. We also find evidence of downsizing, in which SMG activity shifts to lower mass haloes at lower redshifts. In terms of their clustering and halo masses, SMGs appear to be consistent with other star-forming galaxies at a given redshift.